A life away from Lively Streets: providing a platform for a multi-faith church to act as a transformative agent for social spaces in the township of Phumula - Ramos, Nicole (My University, 2020)
Connection is one of the biggest aspects of our lives. Brene Brown, a Professor with her PhD in social work said in an interview that “A deep sense of love and belonging is an irresistible need of all people. We are biologically, cognitively, physically, and spiritually wired to love, to be loved, and to belong. When those needs are not met, we don't function as we were meant to.” I believe architecture can only be successful if designers constantly bare the concept of connection in mind: social connections, cultural connections, physical connections, etc. Architects need to understand what people need and want, what makes them happy. As a future architect myself, I wanted to use this year and thesis to explore this notion of connection as much as I could. The concept of connection in such a diverse country, whose foundations were built on that of segregation and not connection becomes an interesting one. It is for this reason I based my project in a township setting, a product of Apartheids spatial planning. People in townships have managed with limited resources, to create a unique township identity and sense of community that has carried residents through troubling times. ‘Ekasi’ is the term vastly used by people who call townships their home. There is probably a stronger sense of connection within town-ship settings than there is within suburbs. If people were deprived of quality public spaces but make their own, one can easily identify why certain places were chosen and not others, and then build conclusions from there. This is unlike being given a public space and told that this is what you should enjoy. In this thesis I will look at the physical characteristics of a particular township, Phumula, a place where one of my best friends grew up. I will look the streets and public spaces in order to understand how people have overcome this idea of separation that Apartheid sought to impose. However as much as people survive and ‘make do’ with what available, one is can still encourage better connections by improving the spaces that they occur in. My project aims to propose spaces for these connections to occur in and begin unravelling the twisted planning systems apartheid left. It will encourage citizens to continue to thrive in a place that was designed only for survival
A research report proposal submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters of Architecture (Professional), 2020